Fundamental Controls (Dawabit Usuliyyah) in Ibn Qudamah's Book Rawdat al-Nazir (d. 620 AH) Related to commands and prohibitions, and what is disliked what is obligatory. (Islamic Sciences Journal, 2026)
Praise be to Allah, Lord of the Worlds, and may prayers and peace be upon the noblest of creation and messengers, our Prophet Muhammad, and upon his family and all his Companions, and those who follow them in goodness until the Day of Judgment.This study is entitled: “Usuli Controls in the Book Rawdat al Nazir by Ibn Qudamah (d. 620 AH) Related to commands and prohibitions, and what is disliked what is obligatory”. It is submitted to the Journal of the College of Islamic Sciences, Tikrit University.The research consists of an introduction and one main section, which includes a preface and three subsections. The introduction explains the importance of knowledge in general and Islamic jurisprudence in particular, due to its significance for the legally accountable person and its role in improving the individual and society. The preface presents the definition of usuli controls in language and in technical usage. The first subsection discusses usuli controls related to commands and prohibitions. The second subsection discusses usuli controls related to what is disliked. The third subsection discusses usuli controls related to what is obligatory. The study ends with a conclusion, followed by the list of sources and references.
Keywords: Controls, Fundamentals, Command, Prohibition, Disliked, Rawdat Al-Nadhir